SUSTAINABLE DEVELOPMENT DALAM PROGRAM CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN FABER CASTLE - Amalia, Diana; Dian Hutami Rahmawati; Andisa Rizky; Mentari Rangga Frisco M.R (Ilmu Komunikasi, FISIP Universitas Pasundan, 2023)
Corporate social Responsility is a company program as a manifestation of the company's commitment to compliance with regulations and a form of concern for environmental conservation. Carrying out a sustainable CSR program will have a positive impact and greater benefits for both the company itself and related stakeholders. This research focuses on the form of CSR carried out by Faber Castell Indonesia which does not only carry out social responsibility programs, but is already a sustainable development program. The CSR program carried out by Faber Castell is a community empowerment program by making the community economically independent. This study uses qualitative research methods with a constructivist paradigm. The results of this study indicate that there are 3 areas of the community empowerment program carried out by Faber Castell in its CSR program, namely the environmental, educational and socio-economic fields. Of the three areas, the programs implemented all refer to sustainable community empowerment and are not programs that are only carried out once or for one period. It is hoped that the program will be able to become a means for the community to be economically independent.